(3NQjOI GdbUQ hLQjOI GdYUQs - (3eMeO Hf eMeO MGeO GdCUHgGfj, YeGO GdOjf GdcGJH,J (B597 (3g` s
(3ChdgG (B:s
(3bGajI GdYjf ef TgQ GdbGVi CHj HcQ GdCQLGfi ChLSJ ef LeQ jNOc SGWY NhakG Ydi HQO HKZQc fGUY s
(3BNQgG (B:s
(3jfJgi CKfGA JQLeI CHj GdeMGSf eMeO Hf jhSa Hf CHj GdbGSe GdTGT HgPG GdHjJ HQgGf Ojf Gddg ce dc ef jO HjVGA Jedc Qb RgQ GdCfLe s
(3GdfSNI HgG MhGTs
(3cJHJ HQSe NRGfI CMeO GdefUhQ GdPgHis
(3hai ChdgG Jedc HNWg hJMHjS GdbQhjjf SfI (B1001 s
(3jTJed JQGLe TYQ GdYQGb s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B26s
Keywords: (3GdJGQjNs